RAG-mediated recombination is the predominant driver of oncogenic rearrangement in ETV6-RUNX1 acute lymphoblastic leukemia - Papaemmanuil, Elli; Rapado, Inmaculada; Li, Yilong; Potter, Nicola E; Wedge, David C; Tubio, Jose; Alexandrov, Ludmil B; Van Loo, Peter; Cooke, Susanna L; Marshall, John; Martincorena, Inigo; Hinton, Jonathan; et al. (Nature genetics, 2014)
The ETV6-RUNX1 fusion gene, found in 25% of childhood acute lymphoblastic leukemia (ALL) cases, is acquired in utero but requires additional somatic mutations for overt leukemia. We used exome and low-coverage whole-genome sequencing to characterize secondary events associated with leukemic transformation. RAG-mediated deletions emerge as the dominant mutational process, characterized by recombination signal sequence motifs near breakpoints, incorporation of non-templated sequence at junctions, ∼30-fold enrichment at promoters and enhancers of genes actively transcribed in B cell development and an unexpectedly high ratio of recurrent to non-recurrent structural variants. Single-cell tracking shows that this mechanism is active throughout leukemic evolution, with evidence of localized clustering and reiterated deletions. Integration of data on point mutations and rearrangements identifies ATF7IP and MGA as two new tumor-suppressor genes in ALL. Thus, a remarkably parsimonious mutational process transforms ETV6-RUNX1-positive lymphoblasts, targeting the promoters, enhancers and first exons of genes that normally regulate B cell differentiation.
Keywords: rekombinace genetická; tumor supresorové geny; regulace genové exprese u nádorů; Humans; sekvence nukleotidů; Recombination, Genetic; Sequence Analysis, DNA; Molecular Sequence Data; Transcription Factors; Genes, Tumor Suppressor; molekulární sekvence - údaje; fúzní onkogenní proteiny; DNA Copy Number Variations; lidé; Sequence Deletion; Homeodomain Proteins; represorové proteiny; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Gene Library; Oncogene Proteins, Fusion; genetická variace; sekvenční analýza DNA; Genetic Variation; Core Binding Factor Alpha 2 Subunit; Repressor Proteins; sekvenční delece; Base Sequence; homeodoménové proteiny; V(D)J Recombination; variabilita počtu kopií segmentů DNA; transkripční faktory bHLH; Gene Rearrangement; genová přestavba; transkripční faktory; protein PEBP2A2; V(D)J rekombinace; Gene Expression Regulation, Neoplastic; pre-B-buněčná leukemie; genová knihovna; Basic Helix-Loop-Helix Transcription Factors